Spatiotemporal analysis of Anopheles gambiae larval sites and malaria transmission in Djilakh, Central Senegal - Assane Ndiaye; Camille Morlighem; Aminata Niang Diène; Moussa Kane; Abdoulaye Diallo; Fassiatou Tairou; Mohamed Abderemane Nourdine; Pape Cheikh Sarr; Lassana Konaté; Ousmane Faye; Oumar Gaye; El Hadji Amadou Niang; et al. (Malaria Journal)
Abstract Background The progress made against malaria has resulted in a nationwide reduction of the disease burden in Senegal. The observed overall low transmission levels are, however, marked by an important spatial heterogeneity with hotspots subsisting in several parts of the country. This requires the determination of the local and regional factors of the observed disparities for tailored interventions to accelerate malaria elimination everywhere. This study aimed to demonstrate the role of larval breeding sites on malaria epidemiological trends in Djilakh, which is one of the malaria hotspots of the Mbour health district. Methods This study was carried out between 2013 and 2017, during the rainy season (June-November) of each year and surveys per year. The malaria incidence consisted of cases confirmed by RDT and climate data, including the rainfall were retrieved from the Mbour weather station. To assess the impact of larval breeding sites on malaria transmission in Djilakh village, logistic regression under the Poisson models were run. The QGIS 2.2.0 free mapping software was used to generate maps. Results The results showed that mosquito breeding sites found within and in the vicinity of the study village consisted of natural temporary ponds, characterized by clay and clay-sandy soils. The analysis of meteorological and malaria morbidity indicated that malaria transmission is influenced by precipitation. The correlation between malaria morbidity and functioning breeding sites varied throughout the rainy season, depending on the size and stability of the existing breeding sites. The incidence of malaria cases was significantly higher (82.4%; 103/125; P < 0.011; OR = 27.006) in hamlets closer to the breeding sites (less than 500 m), declining gradually with distance with 17.6% (22/125) of the cases recorded in hamlets located between 500 and 1000 m apart from the larval habitats and, no cases in the most remote hamlets (> 1000 m). Conclusions These findings represent a preliminary step towards a better understanding of how the environmental factors influence the persistence of malaria transmission in the studied hotspot villages in Senegal. The generated results indicate a need for targeted control actions in the studied site.